KREASI MEDIA PEMBELAJARAN MATEMATIKA DIGITAL KOLABORASI GENIALLY DAN QUIZWHIZZER UNTUK SISWA SMA KELAS X - Rachmawati, Nadiya Isnaini; Afifah, Ani; Aufin, Muhammad (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to develop and test the validity, practicality and effectiveness in improving student learning outcomes. The research method used is the R&D (Research and Development) method, ADDIE model (analyze, design, development, implementation, and evaluation). The results showed that math learning media using platfrom genially combined quizwhizzer based on the results of material tests (72.63%) and media experts (78.21%) with the Valid category. Based on the practicality test in terms of student observation sheets (71.5%) and teacher observation sheets (76.25%) with good categories. While in terms of the effectiveness of math learning game media in increasing the increase in math learning outcomes, which is 90%. So it can be concluded that the development of mathematics learning media using platfrom genially combined quizwhizzer is very effective in improving student learning outcomes in quadratic equation material. Penelitian ini bertujuan mengembangkan dan menguji kevalidan, kepraktisan serta efektifitas dalam meningkatkan hasil belajar siswa. Metode penelitian yang digunakan yakni metode R&D (Research and Development), model ADDIE (analyze, design, development, implementation, dan evaluation). Hasil penelitian menunjukkan bahwa media pembelajaran matematika menggunakan platfrom genially kombinasi quizwhizzer berdasarkan hasil uji materi (72,63%) dan ahli media (78,21%) dengan kategori Valid. Berdasarkan uji kepraktisan ditinjau dari Lembar observasi siswa (71,5%) dan lembar observasi guru (76,25%) dengan kategori baik. Sementara ditinjau dari efektivitas media game pembelajaran matematika dalam meningkatkan peningkatan hasil belajar matematika yakni sebesar 90%. Maka dapat disimpulkan bahwa pengembangan media pembelajaran matematika menggunakan platfrom genially kombinasi quizwhizzer sangat efektif dalam meningkatkan hasil belajar siswa dalam materi persamaan kuadrat.